Elephant - Fuller, Errol (Princeton, New Jersey : Princeton University Press, 2019)
A lavishly illustrated celebration of these glorious animals--and a poignant lament for their future. Elephants are among the most beloved of all creatures. Their behavior can seem almost human, from their complex social interactions to their need to mourn their dead. They are also among the most persecuted of animals, subjected to untold cruelty at the hands of humans through the ages. In this stunningly illustrated book, Errol Fuller provides a rich and moving portrait of elephants, exploring their natural history, the legends that have grown up around them, their unique place in art and literature, and their urgent need for protection today. Fuller traces the evolution of these majestic animals from prehistoric mammoths and mastodons to today's African and Asian elephants, and looks at their behavior, herd dynamics, and social life. He examines the role of elephants in cultures around the world, from folklore and fine art to the exploitation of elephants as war machines and circus animals. Fuller also discusses the importance of conservation, warning that continued poaching and habitat degradation could send these iconic animals the way of the dodo. Featuring many evocative photos never before published, Elephant is a fittingly exquisite tribute to these breathtaking creatures.
Elephant -- African elephants -- Asian elephants -- In the beginning : evolution, mammoths, mastodons -- Elephant curiosities -- The elephant in art, literature, and popular culture -- Conservation.
Includes bibliographical references (pages 282-283) and index.
Keywords: Elephants; Elephants -- Pictorial works; Elephants -- Effect of human beings on